A collection of abstracts 2: Faculty of Civil Engineering / Universiti Teknologi MARA, UiTM - UiTM, Universiti Teknologi MARA (Faculty of Civil Engineering, UiTM, 2005)
In accordance with the mission of our faculty to develop expertise and provide academic programmes in the field of civil engineering through excellence in research and consultancy, faculty members are encouraged to participate in the research activities and not only being a teaching staff. For the past two years, significant academic writings have been produced through the provision of internal and external grants. This second volume of collection of abstracts is published to keep proper records of knowledge development that are being presented and published in the conferences and journals respectively. Apart from that, it will also act, as a platform to promote our faculty intellectual assets to the market of engineering research and consultancy at the national and international level. The documentation of these abstracts, will serve as a knowledge bridge between senior and junior members of the faculty.